Evaluation of Throughfall Variation under Aegle marmelos, Syzygium cumini and Tamarindus indica in Central Highlands Eco-Region of India - Sahu, M. L. (Indian Forester, 2016)
In-situ rainwater harvesting is foremost step to combat future shortage of water. About 3000 millions trees outside the forest of the country can play pivotal role in in-situ rainwater harvesting. Rainfall is redistributed in the form of stemflow, throughfall and interception loss under vegetation. The throughfall can be recharged into ground water by increasing the opportunity time and by inexpensive land configuration. The major objective of the study was the quantification of throughfall. The study was carried out under the fifteen year old plantation of A. marmelos, S. cumini and T. indica at JNKVV, Jabalpur, Madhya Pradesh, India, during the year 2004 and 2005. The effect of species on throughfall was highly significant. Significantly lower throughfall was noted in T. indica (60.7%) as compare to S. Cumini (74.1%) and A. marmelos (79.1%). The highest (92.1%) and lowest (51.6%) throughfall was recorded respectively in rain class III (5-10 mm) and II (2.5- 5.0 mm) under A.marmelos. The highest (72.5%) and lowest (57.4%) throughfall was respectively in rain class III (5-10 mm) and IV (10-20 mm) under S.cumini. Whereas under T.indica highest (60.2%) and lowest (32.2%) throughfall was observed respectively in rain class I (below 2.5 mm) and II (2.5-5.0 mm).